2022
DOI: 10.1055/s-0042-1751258
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline: An Antibiotic Attenuates Oxidant Stress, Perturbation of Lipid Metabolites, and Antioxidants against Vanadium Toxicity in Rat Hepatocytes

Abstract: Background The liver is target following exposure to pentavalent vanadium (V5+). Doxycycline is an antioxidant that prevents the progression of disease through inhibition of lipid peroxidation. Aim The present study was designed to evaluate the protective effects of doxycycline against vanadium-induced hepatoxicity. Methods Sixty two male Sprague-Dawley rats (250–300 g) were equally divided into the following four groups: control group (received 0.2 mL of physiological saline), doxycycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…5 Another study was performed to examine the effect of intramuscular injection of vitamin D on serum 25-hydroxyvitamin D levels, glycemic control, and liver enzymes in Libyan patients suffering from type 2 diabetes mellitus with vitamin D deficiency. 6 Animal studies included evaluation of the protective effects of doxycycline against vanadium-induced hepatoxicity in rats, 7 and central nervous system effects of the methanolic extract of the leaves of Capparis spinosa L. 8 A clinicopathological characteristics of prostate lesions in surgical specimens of Libyan patients were prescribed in a retrospective study, 9 and a review article provided information on the current state of antimicrobial resistance in Libya. 10 Another original research article reported the magnitude of burnout among physicians in Benghazi-Libya, 11 and a letter to the editor describing the 8th Libyan Cardiac Society Congress Recommendations.…”
mentioning
confidence: 99%
“…5 Another study was performed to examine the effect of intramuscular injection of vitamin D on serum 25-hydroxyvitamin D levels, glycemic control, and liver enzymes in Libyan patients suffering from type 2 diabetes mellitus with vitamin D deficiency. 6 Animal studies included evaluation of the protective effects of doxycycline against vanadium-induced hepatoxicity in rats, 7 and central nervous system effects of the methanolic extract of the leaves of Capparis spinosa L. 8 A clinicopathological characteristics of prostate lesions in surgical specimens of Libyan patients were prescribed in a retrospective study, 9 and a review article provided information on the current state of antimicrobial resistance in Libya. 10 Another original research article reported the magnitude of burnout among physicians in Benghazi-Libya, 11 and a letter to the editor describing the 8th Libyan Cardiac Society Congress Recommendations.…”
mentioning
confidence: 99%